Legal regulation of national security in Ukraine: today’s challenges - Ye. V. Kobko (Law and Safety, 2022)
The article is devoted to the study of the legal regulation of national security in Ukraine. Against the background of the full-scale invasion of Russia on the territory of Ukraine, this issue becomes particularly relevant and requires a more detailed and in-depth study. Moreover, in recent years, the raised issue is becoming more relevant not only on the territory of Ukraine, but also in the field of lively discussion at the international level, because modern legal, democratic states of the world seek to join forces in this direction.